The Effect of the Computer on Problem Solving Skills - Kurshan, Barbara; Williams, Joyce ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1985)
This report presents the results of a study conducted to determine if the use of a microcomputer increases the problem solving ability of junior high school students. Two seventh grade classes from similar schools in the state of Virginia were selected for the study. The first group was exposed to introductory computer literacy skills and simple computer programming exercises for an entire year in a microcomputer laboratory, while the second group was not given computer instruction. The results indicate that the students exposed to computers show increased problem solving ability and that there are some differences in problem solving skills between boys and girls exposed to the computer. It is concluded that the computer is a useful tool for increasing problem solving skills and recommendations are made for curriculum changes and additions, including specific microcomputer software packages and computer activities that could further increase problem solving skills enhanced by the use of the computer. (Author/JB)
Practitioners.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Analysis of Covariance; Computer Assisted Instruction; Computer Literacy; Grade 7.; Junior High School Students; Junior High Schools; Microcomputers; Problem Solving; Sex Differences; Skill Development; Reports, Research